A study of companies' business responses to fashion e-commerce's environmental impact. Issue 2 (4th May 2018) - Bertram, Rose Francoise; Chi, Ting
ABSTRACT: The emerging e-commerce business mode comes with logistical challenges, especially concerning environmental sustainability. Although the environmental effects of e-commerce have drawn attention in recent years, extant knowledge on this issue and possible solutions is very limited. Using the secondary data, this study analysed and compared prior studies regarding the different environmental effects of apparel e-tailing versus traditional retailing in terms of carbon emissions, waste, and energy usage. The focused four parts of the supply chain are packaging, transportation, return, and disposal. Findings showed that, under most circumstances, online shopping is better for the environment than in-store shopping, but intervening factors, such as excessive packaging, shipping speed and/or apparel returns, add more carbon footprint and waste to the environment. As online shopping is becoming progressively more efficient as technology continues to advance, apparel e-tailers have adapted to further create eco-friendly business models that reduce or even reverse negative environmental effects.